Peluang Membangun Spiritualitas Di Era Covid 19 Berdasarkan Nehemia 2:11-20 - Yohanis Kotte (Shalom: Jurnal Teologi Kristen, 2021)
Abstract: The era of the Covid-19 pandemic and the development of the delta variant have urged the United Nations to define this era as the new normal era. Because millions of people have been exposed, died, economic recession, there have been layoffs, the tradition of gathering in certain activities by gathering people in hundreds or even thousands are restricted and must follow the new normal regulations by government recommendations or policies. This study aims to find the basics as an opportunity to build spirituality in the text of Nehemiah 2:11-20 that can be applied during the Covid 19 period. The study uses a library research method by collecting data in the form of documents, theological books, interpretations, and even Bible texts, magazines, articles, and news. The results of his research. There are three opportunities to build spirituality during the Covid 19 pandemic. First: Build facilities and infrastructure for symbols of security and order in carrying out spirituality; second: building vertical (covenant renewal) and horizontal relationships through prayer to God, communicating with the king, building relationships with the people, and acting with precise management according to the times. Third: Opportunity to use modern infrastructure (covid-19 pandemic) real action in managing all virtual and inside implementations.   Abstrak: Era Pandemi Covid 19 dan perkembangan varian delta mendesak Perserikatan Bangsa-bangsa menetapkan era ini sebagai era new normal. Karena Jutaan orang terpapar, meninggal, resesi ekonomi, adanya putus hubungan kerja, tradisi berkumpul dalam kegiatan-kegiatan tertentu dengan mengumpulkan orang dalam jumlah ratusan bahkan ribuan dibatasi dan wajib mengikuti peraturan new normal sesuai dengan anjuran atau kebijakan pemerintah. Penelitian ini bertujuan menemukan dasar-dasar sebagai peluang membangun spiritualitas dalam teks Nehemia 2:11-20 yang dapat diterapkan pada masa Covid 19. Penelitian menggunakan metode penelitian kepustakaan dengan mengumpulkan data berupa dokumen, buku teologi, tafsiran bahkan teks Alkitab, majalah, artikel, dan berita. Hasil penelitiannya. Ada tiga peluang membangun spiritualitas masa pandemi Covid 19. Pertama: Membangun sarana dan prasarana simbol keamanan dan ketertiban dalam menjalankan spiritualitas; kedua: membangun hubungan vertikal (pembaharuan kovenan) dan horizontal melalui doa kepada Allah, berkomunikasi kepada raja, membangun relasi dengan umat dan bertindak dengan manajemen yang jitu sesuai zamannya.  Ketiga: Peluang menggunakan sarana prasarana masa kini (masa pandemi covid 19) tindakan nyata dalam mengelola semua pelaksanaan secara virtual maupun inside.